Comprehensiveness of monotheistic religion of Islam - Ashimi, Tijani Ahmad (2014)
Events in the Muslim world and in the West continue to search for a true meaning of Islam. Indeed, Islam is a religion of peace; it is a religion to lead mankind from the depths of darkness and ignorance towards the path of light and knowledge. The literal meaning of Islam, derived from the Arabic word Salaam, means peace. The word “Islam” has another root derivation – Slim – which means surrender or submission. In short, Islam means peace acquired by humans by submitting their will to the Will of Allah. Moreover, Islam does not only foster love between fellow Muslims; rather it is a merciful for all of humankind. The “peace” of Islam has got many dimensions, ranging from peace with Allah, peace with society and peace with all of mankind irrespective of caste, creed and religion. Islam guides people to the path of non-violence and tolerance and shows the path of righteousness and piety. However, a religion with such high values enshrined in its very name is misunderstood by the bulk of humans as violent and intolerant. Perhaps, this misrepresentation is attributed to tendency of some people who refer to irrelevant source of information about Islam (media). As a matter of fact, the misinterpretation of many mischievous people has given a bad name to this “religion of peace”. But, at this critical point, people should know that Islam is a comprehensive religion, it deals with all aspects of life, ranging from tolerance economy politics, moral values and many more. As such, it is not based on this scholar’s or that scholar’s interpretation, but, it is what the Holy Scripture – the Quran, says and what Muhammad– the Prophet of Islam says and preaches. These are the two primary sources of Islam. Thus, for the sake of conference this humble paper, by applying textual approach will demonstrate the comprehensiveness of Islam as a successful way of life, with particular reference to Islam and tolerance, Islam and politics, and Islam and economics.